Role of H2O2 in the fluctuating patterns of COD (chemical oxygen demand) during the treatment of palm oil mill effluent (POME) using pilot scale triple frequency ultrasound cavitation reactor - Manickam, Sivakumar; Zainal, Norzaini Binti; Parthasarathy, Shridharan; Alzorqi, Ibrahim; Ng, Ern Huay; Tiong, Timm Joyce; Gomes, R.L.; Ali, Asgar (Elsevier, 2014)
Palm oil mill effluent (POME) is a highly contaminating wastewater due to its high chemical oxygen demand (COD) and biochemical oxygen demand (BOD). Conventional treatment methods require longer residence time (10–15 days) and higher operating cost. Owing to this, finding a suitable and efficient method for the treatment of POME is crucial. In this investigation, ultrasound cavitation technology has been used as an alternative technique to treat POME. Cavitation is the phenomenon of formation, growth and collapse of bubbles in a liquid. The end process of collapse leads to intense conditions of temperature and pressure and shock waves which assist various physical and chemical transformations. Two different ultrasound systems i.e. ultrasonic bath (37 kHz) and a hexagonal triple frequency ultrasonic reactor (28, 40 and 70 kHz) of 15 L have been used. The results showed a fluctuating COD pattern (in between 45,000 and 60,000 mg/L) while using ultrasound bath alone, whereas a non-fluctuating COD pattern with a final COD of 27,000 mg/L was achieved when hydrogen peroxide was introduced. Similarly for the triple frequency ultrasound reactor, coupling all the three frequencies resulted into a final COD of 41,300 mg/L compared to any other individual or combination of two frequencies. With the possibility of larger and continuous ultrasonic cavitational reactors, it is believed that this could be a promising and a fruitful green process engineering technique for the treatment of POME.